Luckin Coffee’s Innovative Marketing Strategies in China - Zhao, Tianyu; Halík, Jaroslav, 1961-; Lhotáková, Markéta, 1971-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2025)
This thesis explores Luckin Coffee’s transformative impact on the Chinese coffee market through its innovative marketing strategies, including rapid store expansions, digital convenience model and strategic pricing. By analyzing Luckin Coffee’s approach from its inception in 2017 to its rise as China's largest coffee chain, this thesis identifies some key factors that contributed to its massive market success, including aggressive promotional tactics, extensive use of digital technology and tailored product diversification. Furthermore, this thesis examines the consumer feedbacks from the author’s primary research of questionnaire, and also analyzes some major financial indicators, highlighting some main areas for Luckin Coffee’s continuous improvement.
Vedoucí práce: Jaroslav Halík
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international business - central european business realities [obor dipl. práce]; diplomové práce; master's theses